ASAS LEGALITAS DALAM DOKTRIN HUKUM INDONESIA: PRINSIP DAN PENERAPAN - Dwi Afrimeti Timoera (Program Studi PPKn FIS UNJ & Asosiasi Profesi PPKn Indonesia, 2011)
The principle of legality is a principle which determines that no act which is prohibited and punishable by criminal if not determined in advance in legislation. This principle is usually known as nullum delictum nulla poena sine praevia lege (no offense, no crime without law first. There are four principles of legality that is, the lex scripta (written law), lex chert (which includes criminal law), nonretroaktif (rule not retroactive) and analogy.